Dance, Music, Meter and Groove: A Forgotten Partnership - Fitch, W. Tecumseh (Frontiers in Human Neuroscience, 2016)
I argue that core aspects of musical rhythm, especially "groove" and syncopation, can only be fully understood in the context of their origins in the participatory social experience of dance. Musical meter is first considered in the context of bodily movement. I then offer an interpretation of the pervasive but somewhat puzzling phenomenon of syncopation in terms of acoustic emphasis on certain offbeat components of the accompanying dance style. The reasons for the historical tendency of many musical styles to divorce themselves from their dance-based roots are also briefly considered. To the extent that musical rhythms only make sense in the context of bodily movement, researchers interested in ecologically valid approaches to music cognition should make a more concerted effort to extend their analyses to dance, particularly if we hope to understand the cognitive constraints underlying rhythmic aspects of music like meter and groove.